Protective Effects of Methanolic Extracts of *Calotropis gigantea* Leaves, Stem Bark and Roots against Diabetes-Induced Hepatic and Renal Dysfunction in Streptozotocin-Induced Albino Rats - Mercy iliya Tumba; Isaac John Umaru; Chinedu Imo (African Journal of Biochemistry and Molecular Biology Research, 2026)
Calotropis gigantea is widely used in traditional medicine, but comparative evidence concerning the antidiabetic and organ-protective effects of its different anatomical parts remains limited. This study evaluated the phytochemical constituents and therapeutic effects of methanolic extracts derived from the leaves, stem bark, and roots of C. gigantea in streptozotocin (STZ)-induced diabetic albino rats. Plant materials were air-dried, pulverized, extracted through cold maceration in methanol for 72 hours, and concentrated using a rotary evaporator. Phytochemical constituents were characterized by gas chromatography–mass spectrometry (GC–MS). Thirty-six male albino rats were randomly allocated to six groups: normal control, diabetic control, metformin-treated (100 mg/kg), and leaf-, stem-bark-, and root-extract-treated groups (100 mg/kg each). Treatments were administered for 14 days. Fasting blood glucose, liver and kidney function indices, and lipid profiles were assessed, alongside histopathological examination of liver and kidney tissues. GC–MS identified several bioactive constituents, including 7-octen-2-ol, α-terpineol, and D-limonene. Diabetes induction increased fasting blood glucose from 4.93 ± 0.25 to 16.14 ± 0.98 mmol/L, with concentrations remaining elevated in untreated diabetic rats. All extracts significantly reduced blood glucose, while the root extract produced the greatest reduction, from 15.37 ± 1.10 to 8.93 ± 1.94 mmol/L, comparable to the response observed with metformin. The root and leaf extracts produced the strongest improvements in renal function indices. The leaf extract yielded the most pronounced reductions in alanine aminotransferase, aspartate aminotransferase, and alkaline phosphatase activities and improved the lipid profile by reducing serum triglyceride and cholesterol concentrations while increasing high-density lipoprotein concentrations. Histopathological findings corroborated the biochemical results, demonstrating reduced hepatic and renal tissue damage in treated animals. These findings indicate that C. gigantea extracts, particularly those obtained from the roots and leaves, possess antidiabetic, hepatoprotective, nephroprotective, and lipid-modulating potential, supporting their further pharmacological evaluation for managing diabetes-associated complications.